2017
DOI: 10.1002/stem.2650
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cells Stabilize Axonal Transports for Autophagic Clearance of α-Synuclein in Parkinsonian Models

Abstract: Genome-wide association studies have identified two loci, SNCA and the microtubule (MT)-associated protein tau, as common risk factors for Parkinson's disease (PD). Specifically, α-synuclein directly destabilizes MT via tau phosphorylation and induces axonal transport deficits that are the primary events leading to an abnormal accumulation of α-synuclein that causes nigral dopaminergic cell loss. In this study, we demonstrated that mesenchymal stem cells (MSCs) could modulate cytoskeletal networks and traffick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 68 publications
0
25
0
Order By: Relevance
“…Dysfunctional mitochondria produce less ATP and more ROS, and because of the high energy demand in the synaptic compartment, lowering ATP leads to synaptic dysfunction (Rangaraju et al 2014) and triggers aSyn accumulation (Nakata et al, 2012). In addition, mitochondrial health correlates with axonal transport, regeneration (Smith and Gallo, 2018), and, consequently, the clearance of aSyn (Oh et al, 2017). Similarly, increased ROS levels facilitate aSyn aggregation (Tabner et al, 2006;Fernandes et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Dysfunctional mitochondria produce less ATP and more ROS, and because of the high energy demand in the synaptic compartment, lowering ATP leads to synaptic dysfunction (Rangaraju et al 2014) and triggers aSyn accumulation (Nakata et al, 2012). In addition, mitochondrial health correlates with axonal transport, regeneration (Smith and Gallo, 2018), and, consequently, the clearance of aSyn (Oh et al, 2017). Similarly, increased ROS levels facilitate aSyn aggregation (Tabner et al, 2006;Fernandes et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that MSCs can migrate to injury sites and secrete various neurotrophic factors that exert neuroprotective effects [15,24], via anti-apoptotic [25], supportive (i.e., stimulation of mitosis, proliferation, and differentiation) [26], and angiogenic effects [25]. In our previous experimental studies, we have demonstrated the therapeutic potential of MSCs in animal models of parkinsonian disorders through antiin ammatory action [27], autophagy modulation [28], stabilization of axonal transport [18], control of microglia M2 polarization [29], proteolysis of α-synuclein aggregates [17], and inhibition of α-synuclein transmission [16], which might modulate α-synuclein-related microenvironments. Furthermore, in two previous clinical trials [12,13], we demonstrated the safety and clinical e cacy of intra-arterial and intravenous administration of autologous BM-MSCs in patients with MSA-C.…”
Section: Discussionmentioning
confidence: 96%
“…To ensure that patients with relatively early-stage MSA were enrolled, the following inclusion criteria were implemented: (1) total Uni ed MSA Rating Scale (UMSARS) score between 30 and 50; (2) disease duration of < 5 years since MS diagnosis. The other inclusion criteria were (1) age between 30 and 75 years; (2) supportive ndings from structural and/or functional imaging studies at the time of diagnosis (i.e., cerebellar atrophy on brain magnetic resonance imaging [MRI] or decreased glucose metabolism in the cerebellum on 18 (2) diagnosis of dementia according to the DSM-IV criteria; (3) severe white matter hyperintensities or cerebrovascular lesions on brain MRI; (4) mutations in spinocerebellar ataxia type 1, 2, 3, 6, 7, 8, and 17 genes; (5) other major neurological disorders (e.g. stroke or brain surgery); (6) severe medical comorbidities (e.g.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…MSCs) a potential therapeutic tool for central nervous system (CNS) applications [48][49][50][51][52]. Indeed, the capacity to adapt and grow into different culture conditions indicates that MSCs could be able to change/modulate their own secretome according with the conditions in which they are cultured [53][54][55]. Besides the secretome modulation at the intracellular level, the modulation of external cues present in cells' microenvironment and their impact on paracrine signaling have also been explored (Figure 1).…”
Section: Modulation Of Cell Secretome Profilementioning
confidence: 99%